2010
DOI: 10.1002/ejoc.200901149
|View full text |Cite
|
Sign up to set email alerts
|

Tetra[6,7]quinoxalinoporphyrazines: The Effect of an Additional Benzene Ring on Photophysical and Photochemical Properties

Abstract: Synthetic methods for a series of zinc tetra[6,7]quinoxalinoporphyrazines (6,7‐TQP) with peripheral chains connected through the S, O and N heteroatoms as well as through the C–C bond were developed. Photophysical and photochemical properties of 6,7‐TQP were compared with tetrapyrazinoporphyrazines (TPP) bearing the same peripheral substituents to disclose the effect of insertion of a benzene ring between the pyrazine and porphyrazine moieties. The influence of the peripheral heteroatom in the group of 6,7‐TQP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Syntheses of precursors 1 53 and 3 54 as well as macrocycles TPyzPz, 55 6,7-TQPz, 54 and Pc 55 Synthesis of 6,7-bis(tert-butylsulfanyl)quinoxaline-2,3dicarbonitrile (6). Compound 9 (2.9 g, 7.7 mmol, for synthesis of 9 see ESI) was dissolved in DMF (80 mL), and sodium ptoluenesulfinate (1.37 g, 7.7 mmol) was added followed by KCN (poison!)…”
Section: Synthesismentioning
confidence: 99%
“…Syntheses of precursors 1 53 and 3 54 as well as macrocycles TPyzPz, 55 6,7-TQPz, 54 and Pc 55 Synthesis of 6,7-bis(tert-butylsulfanyl)quinoxaline-2,3dicarbonitrile (6). Compound 9 (2.9 g, 7.7 mmol, for synthesis of 9 see ESI) was dissolved in DMF (80 mL), and sodium ptoluenesulfinate (1.37 g, 7.7 mmol) was added followed by KCN (poison!)…”
Section: Synthesismentioning
confidence: 99%
“…The synthesis of most of the precursors (6 -11) 12,14,[17][18][19][20] (Scheme 1) was performed according to previously published protocols. The synthesis of most of the precursors (6 -11) 12,14,[17][18][19][20] (Scheme 1) was performed according to previously published protocols.…”
Section: Synthesismentioning
confidence: 99%
“…The treatment of the statistical mixture of magnesium complexes with p-toluenesulfonic acid (TsOH) in THF at room temperature afforded a mixture of metal-free complexes that typically do not tail. [17][18][19][20] Electrochemistry 12 Indeed, the conversion of the mixture of magnesium derivatives to metal-free derivatives significantly facilitated the separation, and AAAB type congeners 2H -5H were isolated in yields ranging from 9 % to 16 %.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral substitution plays a crucial role in defining the properties of AzaPc and Pc derivatives. It has been shown that alkylsulfanyl‐10 and alkyloxy‐substituted11,12 AzaPcs are characterized by high singlet oxygen ( Φ Δ ) and fluorescence quantum yields ( Φ F ), which makes them ideal candidates for cancer treatment by PDT, or fluorescence detection. On the other hand, alkylamino substitution leads to values of almost zero for both Φ F and Φ Δ because of effective intramolecular charge transfer 13.…”
Section: Introductionmentioning
confidence: 99%